Big data and business analytics - Liebowitz, Jay, 1957- (CRC Press, 2013)
""The chapters in this volume offer useful case studies, technical roadmaps, lessons learned, and a few prescriptions to 'do this, avoid that.'""--The Foreword by Joe LaCugna, Ph. D., Enterprise Analytics and Business Intelligence, Starbucks Coffee CompanyWith the growing barrage of ""big data, "" it becomes vitally important for organizations to make sense of this data and information in a timely and effective way. That's where analytics come into play. Research shows that organizations that use business analytics to guide their decision making are more productive and experien